Which ‘being’ in wellbeing? Ontology, wellness and the geographies of happiness - Smith, Thomas S.J.; Reid, Louise (Progress in human geography, 2018)
This article examines current approaches to wellbeing research in the social sciences, reviewing their underlying ontologies to explore which ‘being’ is implied in contemporary research on wellbeing. It critically analyses themes from the ‘science of happiness’ for their focus on a decontextualized and individualized subject and highlights the emergence of an alternative, developing geographical research agenda in the study of wellbeing, termed here ‘intra-active wellbeing’. It is argued that this research agenda draws together formerly disparate aspects of geographical thought – classically humanistic wellbeing research and more-than-human inquiry – and creates space for a more pluralistic field of wellbeing scholarship.